Comparative pathogenesity of Fusarium species on some of the potato cultivars. - Esfahani, Mehdi Nasr (Plant Breeding and Seed Science, 2011)
The fusarium dry rot is one of the most important diseases of potato tubers causing considerable damages during the storage. Resistance sources are one of the fundamental methods in prevention and disease control. This study details the pathogenesity and assessment of susceptibility of commercially acceptable potato Cultivars to dry rot causing by Fusarium sulphureum , F. solani and F. oxysporum under similar conditions includings . inoculum , mehtod of inoculation, temperature , relative humidity and light. The results indicated that though the similar conditions were applied, the tubers of varieties reacted with differing levels of resistance to the species causing the disease. It was found that F. sulphureum was the most aggressive one, then fallowed by F. solani as far as the disease development is concerned and were independent. F. oxysporum did not cause considerable damages. In these expriments the commerical potato varieties were Seuminar, Rustica, clivastave, Dital, Escort, Monalisa, Marfona, Mondial, Aniona, Deraga, Asta, Hidram, Melisa, Moren, Mariyana, Pashandi, Frasco, Alva, Ceaser, Asva, Aula, Sandara , Marijke, Folva, Tiva, Fregate, Baraka, Aida, Diamant, Arnica, Panda, Atlas, Erigo, Volkano, Famosa, Carlita, Korrigan, Casmos, Assour, Cosima, Ariane, Desiree and saturna, in which started with most susceptible ones fallowed to resistance ones at end to F.sulphureum. The variety saturna were the most resistant one to the all tested species in these expriments.